Morphological and Phenological Response of African Rice (Oryza glaberrima Steud.) under Different Hydrological Conditions - Montcho, D.; Futakuchi, K.; Agbangla, C.; Semon, M.; Dieng, I.; Sie, M. (Science Alert, 2013)
Oryza glaberrima is often classified into two ecological groups: upland and floating types. To assess the phenotypic variability of O. glaberrima across hydrological conditions, 217 accessions and 5 checks (Oryza sativa) were cultivated using toposequence. The trial was conducted at the experimental field of the International Institute of Tropical Agriculture in Ibadan during the wet seasons in 2009 and 2010. An Alpha Lattice design with three replications was used. Phenotypic data including vegetative vigor, plant height and tillers number at maturity, days to 50% heading and crop duration were recorded. The results indicated high variability among all O. glaberrima tested across ecologies for plant height, tiller ability and crop duration. This variability was confirmed by low genetic correlation coefficients, which demonstrated the significance of genotype by environment interaction. Oryza glaberrima accessions tested showed best vegetative vigor from upland to lowland. In 2009, 77.5 and 82.2% of the accessions were tall in hydromorphic and lowland, respectively while they represented 87.5 and 84.8%, respectively in 2010. Tillers number was intermediate from upland to lowland in both years. Result in 2009 indicated that 54.5% in upland, 70.9% in hydromorphic and 45.3% in lowland of O. glaberrima were intermediate tillering. The second season showed 63.2% in upland, 79.1% in hydromorphic and 82.1% in lowland. High percentage of O. glaberrima accessions was observed as late and very late maturing in 2009, 89.9% in upland and 91.4% in lowland. This study support efforts to breed for phenological plasticity in any rice growing environment.